2021
DOI: 10.1038/s41467-020-20303-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-specific IL11 cis-signaling drives lipotoxicity and underlies the transition from NAFLD to NASH

Abstract: IL11 is important for fibrosis in non-alcoholic steatohepatitis (NASH) but its role beyond the stroma in liver disease is unclear. Here, we investigate the role of IL11 in hepatocyte lipotoxicity. Hepatocytes highly express IL11RA and secrete IL11 in response to lipid loading. Autocrine IL11 activity causes hepatocyte death through NOX4-derived ROS, activation of ERK, JNK and caspase-3, impaired mitochondrial function and reduced fatty acid oxidation. Paracrine IL11 activity stimulates hepatic stellate cells a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 42 publications
6
116
0
Order By: Relevance
“…In conclusion, loss of IL11 signaling due to mutation in either Il11 or Il11RA1 is protective against lung fibrosis that relates to reduced autocrine IL11 activity in myofibroblasts 14 , 30 . However, the craniosynostosis and bone phenotypes seen in Il11RA1 deficient mice are not seen in Il11 − / − mice, suggesting that developmental, STAT3-related bone effects are not due to defective IL11 signaling per se and instead, specific to Il11RA1 LOF.…”
Section: Discussionmentioning
confidence: 92%
“…In conclusion, loss of IL11 signaling due to mutation in either Il11 or Il11RA1 is protective against lung fibrosis that relates to reduced autocrine IL11 activity in myofibroblasts 14 , 30 . However, the craniosynostosis and bone phenotypes seen in Il11RA1 deficient mice are not seen in Il11 − / − mice, suggesting that developmental, STAT3-related bone effects are not due to defective IL11 signaling per se and instead, specific to Il11RA1 LOF.…”
Section: Discussionmentioning
confidence: 92%
“…Accumulating evidence has suggested that the pathological remodeling response is coordinated with oxidative stress, inflammation, apoptosis and numerous signaling pathways. Jinrui Dong's study showed that IL-11 activity causes hepatocyte death through NOX4-derived ROS, activation of ERK, JNK and caspase-3, impaired mitochondrial function and reduced fatty acid oxidation [ 51 ]. Anissa A. Widjaja's study discovered an unexpected proinflammatory role for IL-11 in the liver [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…While earlier reports demonstrated that recombinant human IL-11 protects from hepatocyte damage induced by oxidative stress, drugs, or ischemia/reperfusion [51][52][53][54], more recent reports show that IL-11 rather promotes liver damage via ROS production [20], activates HSCs [19,20], and hence, promotes liver fibrosis in the setting of chronic liver disease. Similarly, OSM was shown to prevent hepatocyte damage by oxidative stress [55][56][57] and to promote hepatic fibrosis by upregulation of TGFβ and PDGF in hepatic macrophages [58], and by stimulating myofibroblast migration [59].…”
Section: Physiological Role Of Il-6 Family Cytokines In the Livermentioning
confidence: 98%
“…During chronic liver disease also senescent hepatocytes and BECs secrete IL-6 (see also below), while OSM is also secreted by hepatic progenitor cells [18]. IL-11 is secreted by activated HSCs [19] [20] and lipidloaded hepatocytes [20] in the course of non-alcoholic fatty liver disease (NAFLD).…”
Section: The Cellular Landscape Of Il-6 Family Cytokine Sender and Receiver In The Livermentioning
confidence: 99%